Platelet P2Y12 Inhibitor Monotherapy after Percutaneous Coronary Intervention: An Emerging Option for Antiplatelet Therapy De-escalation - Verheugt, Freek W. A.; Huber, Kurt; Clemmensen, Peter; Collet, Jean-Philippe; Cuisset, Thomas; Andreotti, Felicita (Thrombosis and Haemostasis, 2022)
Antiplatelet therapy is considered essential for secondary prevention of ischemic heart disease. After percutaneous coronary intervention (PCI), temporary dual antiplatelet therapy (DAPT), a combination consisting of aspirin and an oral P2Y12 receptor blocker, is recommended. In the long term, this strategy results in more bleeding than antiplatelet therapy with aspirin alone. Therefore, to reduce bleeding, an increasing trend has been to keep DAPT as short as clinically acceptable, after which aspirin monotherapy is continued. Another option to diminish bleeding is to discontinue aspirin at the moment of DAPT cessation after PCI, and to continue on P2Y12 blocker monotherapy. This survey reviews the evidence on P2Y12 blocker monotherapy. Some clinical guidance will be provided on when and in whom P2Y12 inhibitor monotherapy may be applied after DAPT cessation following PCI.
Keywords: aspirin; clopidogrel; ticagrelor; prasugrel; percutaneous coronary intervention